Antibacterial properties of Au doped polycarbonate synthesized by gamma radiation assisted diffusion method. (July 2015) - Hareesh, K.; Deore, Avinash V.; Dahiwale, S.S.; Sanjeev, Ganesh; Kanjilal, D.; Ojha, Sunil; Dhole, N.A.; Kodam, K.M.; Bhoraskar, V.N.; Dhole, S.D.
Abstract: Gold (Au)–Polycarbonate (PC) matrix was prepared by gamma radiation assisted diffusion of Au nanoparticles in PC matrix. UV–Visible spectroscopy showed the surface plasmon resonance around 550 nm which corresponds to Au and this peak shift towards lower wavelength i.e. blue shift indicating the decrease in particle size of Au. Rutherford Backscattering (RBS) experiment confirmed the diffusion of Au in PC and depth of diffusion is found to be around 0.85 µm. X-ray Diffractogram (XRD) results also revealed the diffusion of Au in PC where the peak observed at 2 θ ∼38.29° which correspond to the FCC structure. Scanning Electron Microscope (SEM) images showed the hexagonal shaped Au nanoparticles and average particle size is found to be around 110 nm. These samples also showed anti-bacterial properties with both gram positive and gram negative bacteria's and revealed the inhibition of the overall growth of the bacteria with gamma dose. Highlights: Au–PC matrix has been synthesized by gamma assisted diffusion method. RBS study showed the diffusion depth of gold in PC as ∼0.85 µm. This depth of diffusion of Au in PC is suspected for the study of anti-bacterial. The prepared Au–PC samples showed moderate anti-bacterial properties.